ANALISIS KEPATUHAN DIET TERHADAP PERUBAHAN KADAR GULA DARAH DALAM TUBUH PADA PASIEN DIABETES MILITUS - Sherly Widianti; Fera Siska (Jurnal Kesehatan dan Pembangunan, 2024)
Diabetes is a metabolic disorder characterized by increased blood glucose as a result of impaired insulin production or impaired insulin work or both because until now there is no drug that can treat the disease. The aim of this study was to analyze dietary compliance with changes in blood sugar levels in diabetes mellitus sufferers. This research was conducted using a qualitative descriptive research method. This research was carried out at the Kenten Permai Public Health Center, Palembang. Qualitative data analysis was inductive, then developed into a hypothesis. In this qualitative research, the number of informants was 3 diabetes mellitus patients and 1 expert informant, namely a nutritionist. Based on the research results, it can be concluded that there is one respondent whose diet is compliant, one respondent who is close to compliant and there is a respondent who is not compliant. D is close to adhering to the schedule but not with the quantity and type, the initial blood sugar was 186mg/dl to 160mg/dl. Mrs. R, who complied with the amount and type with her initial clock of 213 mg/dl, became 136 mg/dl. Mrs. R, who was less compliant, experienced a very slight decrease in blood sugar from 328 mg/dl to 298 mg/dl. All respondents knew about the diabetes mellitus diet, and began to apply it in their daily lives.